Magnesite resources and prospects for the development of new applications of magnesite raw materials in the light of energy transition and strategic needs of the EU raw materials economy - Baic, Ireneusz; Kozioł, Wiesław; Miros, Artur; Zawalski, Marek (Gospodarka Surowcami Mineralnymi – Mineral Resources Management, 2026)
The article presents the current state of domestic and global resources of magnesite deposits, potassium-magnesium salts, and magnesium sulfate salts. The volumes of extraction and production of magnesite raw materials, as well as the directions and tendencies of their consumption, are also presented. Compared to the size and quality of the world’s magnesite and magnesium sulfate salts resources, Poland has relatively limited production capacities for magnesite raw materials, especially of high quality. New, promising prospects are the deposits of sulfate salt-type (polyhalite), which occur in the area of the Bay of Puck. They are currently being more thoroughly identified and documented. This type of salt is increasingly used in the production of, among other things, magnesium building materials (Qi 2025; Zhou et al. 2025). The use of building materials produced with the use of magnesite raw materials, in particular magnesium slabs, blocks, and cements, is gaining importance in modern construction. These products are distinguished by their high fire resistance, moisture resistance, and biodegradability, which makes them the materials of choice for construction considerations requiring durability and safety. The EU’s energy transition program and the need to reduce dependence on external sources of natural resources create new directions for the use of magnesite raw materials, such as hydrogen storage or new technologies for the production of metallic magnesium. The inclusion of magnesite raw materials in national value chains – from refractories, through advanced construction technologies, to the hydrogen economy – should become an element of a conscious industrial policy.